FENOMENA PENGELOMPOKAN BUAH DAN SAYUR:PERSPEKTIF SEMANTIK LEKSIKAL - Dea Nur Zalika; Muhammad Arie Andhiko Ajie (EPIGRAM (e-journal), 2023)
This study aims to understand the phenomenon of fruit dan vegetable grouping through a lexical semantic point of view, particularly Componential Analysis and  Componential Analysis of Meaning. Through these theories, the types of meaning components found in the data are described, namely common components and diagnostic components. This research uses qualitative research with the simak and catat method. Sources of data were obtained from articles which mentioned several overlapping food objects. Those object is used as a source of questionnaire research. The questionnaire consists of two parts. The first part contains grouping fruits or vegetables on overlapping food objects. The second part contains the reasons of respondents in determining the selected objects as fruits or vegetables. The research data in the form of reasons for choosing fruits or vegetables were analyzed based on Componential Analysis and then analyzed for their Meaning Components. The criteria for respondents in this study were men and women who are currently studying or have already finished their bachelor degree.The results showed that there are nine common components and one diagnostic component. Common components between fruits and vegetables are [BIJI], [DAUN], [AKAR], [BATANG], [KULIT HIJAU], [KULIT WARNA-WARNI], [MENTAH], [DIMASAK], DIKUPAS]. The diagnostic component between the fruit and vegetable is [DAGING BUAH]. In addition, there are differences of diagnostic components which are believed between one and the other group to be one of the factors in the phenomenon of fruit and vegetable grouping which does not find common ground in every discussion.